Video-assisted pulmonary metastectomy is equivalent to thoracotomy regarding resection status and survival - Markowiak, Till (J Cardiothorac Surg, 2021)
BACKGROUND: Surgical resection of pulmonary metastases leads to prolonged survival if strictly indicated. Usually, thoracotomy with manual palpation of the entire lung with lymph node dissection or sampling is performed. The aim of this study was to evaluate the role of video-assisted thoracoscopic surgery (VATS) in pulmonary metastectomy with curative intent. METHODS: In this study, all patients with suspected pulmonary metastasis (n = 483) who visited the Center for Thoracic Surgery in Regensburg, between January 2009 and December 2017 were analysed retrospectively. RESULTS: A total of 251 patients underwent metastectomy with curative intent. VATS was performed in 63 (25.1%) patients, 54 (85.7%) of whom had a solitary metastasis. Wedge resection was the most performed procedure in patients treated with VATS (82.5%, n = 52) and thoracotomy (72.3%, n = 136). Postoperative revisions were necessary in nine patients (4.8%), and one patient died of pulmonary embolism after thoracotomy (0.5%). Patients were discharged significantly faster after VATS than after thoracotomy (p < 0.001). Complete (R0) resection was achieved in 89% of patients. The median recurrence-free survival was 11 months (95% confidence interval 7.9–14.1). During follow-up, eight (12.7%) patients in the VATS group and 42 (22.3%) patients in the thoracotomy group experienced recurrence (p = 0.98). The median overall survival was 61 months (95% confidence interval 46.1–75.9), and there was no significant difference with regard to the surgical method used (p = 0.34). CONCLUSIONS: VATS metastasectomy can be considered in patients with a solitary lung metastasis. An open surgical approach with palpation of the lung showed no advantage in terms of surgical outcome or survival.